(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2023)
The purpose of the study was to clarify the signs symbols and meanings of symbols contained in mineral water product advertisements using Charles S. Pierce’s semiotic theory. And also to found out the influence of mineral water advertising on consumers. The research used a qualitative method. Data analysis techniques used in the research were observation, interviews, and documentation. The research described the symbols of various video scans of mineral water advertisements and symbol messages contained in mineral water advertisements. There was a different symbol meaning for each video ad scan. and also found out how the influence of advertising on interest in buying mineral water by conducting interviews with customers or consumed mineral water. Researchers also found that consumed mineral water depended on advertising and taste.